Penerapan Hidroterapi untuk Menurunkan Tekanan Darah pada Lansia dengan Hipertensi - Susanti, Yunita Dwi; Ulfah, Mariah; Kurniawan, Wasis Eko (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: Hypertension is a condition of systolic blood pressure >140 mmHg and diastolic blood pressure >90 mmHg that often affects the elderly. One way to overcome this is with hydrotherapy by soaking the feet in warm water. Objective: The aim of this community service is to increase the knowledge and abilities of elderly people with hypertension, while also helping to lower their blood pressure. Method: The community service activity was conducted at Posbindu Lestari Husada 2, Purwareja Village, in May 2025 using lecture and demonstration methods with PowerPoint and leaflet media. Participants were hypertensive older adults aged ≥45 years who met the inclusion criteria. The instruments included a knowledge questionnaire, a self-monitoring sheet for hydrotherapy practice, and a blood pressure measuring device. Data were analyzed descriptively and tested using the Wilcoxon Signed Rank Test to determine differences in knowledge before and after the education. Result: The results of this activity showed changes in knowledge and blood pressure after two meetings seven days apart. with the proportion of participants with adequate knowledge increasing from 9 individuals (31.0%) to 24 individuals (82.8%), and a reduction in the number of participants with severe hypertension from 4 individuals (13.8%) to 0 individuals (0.0%), with an average systolic blood pressure of 14 and diastolic blood pressure of 5.65. Conclusion: The use of hydrotherapy has been proven effective in lowering blood pressure in patients with hypertension.